Proyecto urbano integral del rio Subachoque en la zona cenro de Madrid Cundinamarca - Torres Abril, Laura Valentina; Trujillo Bohórquez, Olga Tatiana (Universidad Antonio Nariño, 2024)
The objective of this work is the recovery and integration of the Subachoque River taking as its main adaptation the polygon 1 of intervention, which is located in the central area of the municipality of Madrid Cundinamarca, where it is directly affected by the disorder, misuse of spaces and insecurity of the sector.